Differences in Security Strategies between China and Japan and the Diaoyu Islands Dispute in the New Era - Liu, Jun (International Journal of Global Economics and Management, 2024)
The Diaoyu Islands dispute is an important part of the Sino-Japanese conflict and has a significant negative impact on the development of Sino-Japanese friendly relations. To better maintain the healthy development of Sino-Japanese relations, we need not only to comprehensively analyze the ins and outs of the Diaoyu Islands issue, but also to explore the Diaoyu Islands issue from a macro perspective based on the differences and contradictions in the security strategies of China and Japan, so as to have a deeper understanding of the historical complexity and current difficulties of the Diaoyu Islands issue and thus propose more effective solutions.